(3GdhLjR TQM GdLGeY GdUZjQ deMeO Hf GdMSf GdTjHGfis - (3hLeGd GdOjf CHi GdeMGeO eMehO Hf CMeO Hf YHO GdSjO GdHNGQj GdMUjQis; (3CHh YHO Gddg eMeO Hf GdMSf Hf aQbO, GdTjHGfj,J (B189 (3g` s
(3BNQgG (B:s
(3jfJgi HHGH GdGjeGf ai GbJVGA GdeGd s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B80s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B9 - (3U (B276 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B568s
Keywords: (3Gdabg GdMfajs